Organizational Innovation Capabilities. Empirical Evidence from b2b Contexts - Marinao-Artigas, E (UNIV ICESI, 2021)
The aim of the article is to explore organizational innovation capability variables that could have an impact on performance in business to business [B2B] context. This work used systematic analysis of the literature supported through bibtiometric analysis indicating the following organizational innovative capabilities: innovation strategy and management projects, collaborative networks and market orientation. The authors propose an explanatory model and provide empirical evidence from B2B sector in Chile, surveying 242 senior executives. The best position was the mining sector. However, all the sectors studied need more emphasis on market orientation, value co-creation and innovation to obtain better and more sustainable results.